1981
DOI: 10.1136/jnnp.44.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Homovanilic acid in Huntington's disease and Sydenham's chorea.

Abstract: SUMMARY Homovanilic acid (HVA) was determined in the lumbar CSF of 12 patients with Huntington's disease and 12 with Sydenham's chorea before and after probenecid administration. The means of HVA concentration (basal and after probenecid) were lower in those with Huntington's disease than in controls, and were even lower in a sub-group characterised by increased tone and slowness of voluntary movement. There was no correlation between CSF HVA values and the severity of abnormal movements, nor with length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Some of the dopaminergic alterations were also seen in non-striatal regions such as hippocampus and frontal cortex, underlining the early aberrant connectivity of dysfunctional frontostriatal circuits in HD [22] . Likewise, several studies reported decreased CSF levels of HVA in HD patients prior to the HTT gene identification [23] , [24] , [25] . Importantly, we showed for the first time that the DA loss was preceded by altered DA metabolism, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…Some of the dopaminergic alterations were also seen in non-striatal regions such as hippocampus and frontal cortex, underlining the early aberrant connectivity of dysfunctional frontostriatal circuits in HD [22] . Likewise, several studies reported decreased CSF levels of HVA in HD patients prior to the HTT gene identification [23] , [24] , [25] . Importantly, we showed for the first time that the DA loss was preceded by altered DA metabolism, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…In an effort to characterize the metabolome, several studies have demonstrated catabolic changes considered as possible biomarkers of progression 16 . Among these, few consistent patterns have emerged, with discrepant data for amino acids [17][18][19][20][21][22][23][24][25][26] , catecholamine metabolites 27,28 , and lipids 23,29,30 . It is not well established how metabolomic changes correlate to clinical outcome measures over the spectrum of early to advanced manifest disease.…”
mentioning
confidence: 99%
“…Nevertheless, the results of studies have varied from showing an elevation of HVA to a reduction in accumulation after probenecid administration. 49,50 Autoimmune Hypothesis: An autoimmune hypothesis has been proposed as the underlying mechanism in Sydenham's chorea; that is, after a streptococcal infection in susceptible individuals, antibodies directed against bacterial antigens cross-react (molecular mimicry) with epitopes on neurons of the basal ganglia and possibly frontal lobes causing choreiform movement abnormalities and behavioral disturbances. Evidence supporting an antineuronal hypothesis in Sydenham's chorea is primarily based on studies by Husby and colleagues who used an immunofluorescent antibody technique to detect tissue-specific antibodies; sera were applied to frozen sections of human brain, a secondary conjugated antihuman IgG antibody was added, and the extent of fluorescence was determined.…”
Section: Pathophysiologymentioning
confidence: 99%